A new species of xylophilic fireworm (Annelida: Amphinomidae: Cryptonome) from deep-sea wood falls in the SW Atlantic. (July 2018) - Barroso, Rômulo; Kudenov, Jerry D.; Halanych, Kenneth M.; Saeedi, Hanieh; Sumida, Paulo Y.G.; Bernardino, Angelo F.
Abstract: Wood-falls are an abundant source of food to the deep-sea along continental margins that host high species diversity and specialized food webs. The colonization and degradation of wood-falls by specialist and generalist infauna has been increasingly recognized as an important factor affecting alpha and beta diversity in the deep-sea. Here we describe a new 'fireworm' species of the genus Cryptonome, family Amphinomidae (Annelida), which was recently discovered in experimental wood-falls of the deep SW Atlantic. Currently, Cryptonome is represented by only three species, including two restricted to the Mediterranean Sea ( C. turcica and C. conclava ) and a third historically characterized as 'circumtropical' ( C. parvecarunculata ); all are associated with submerged wood. Our new taxon possesses harpoon chaetae with two rows of barbs; Cryptonome is here emended to include this character and its ontogenetic variation. The presence of multiple barb-rows on harpoon notochaetae is noteworthy since, until now, this feature was thought to be unique to the genus Amphinome. Cryptonome barbada sp. nov. represents the first report of this genus for deep-sea wood-falls in the SW Atlantic and differs from its congeners by the presence of harpoon notochaetae with two barb-rows, and the absence of both eyes and spurred notocapillaries. The assembled complete mitochondrial genome of C. barbada sp. nov. is herein presented and has an identical gene order and high similarity in base composition with previous amphinomid mtDNA data. Mitochondrial CO1 and 16S sequences of C. barbada sp. nov. were compared with those of related taxa with available sequences, further supporting the placement of this new species within the genus Cryptonome . Highlights: New fireworm has been described from wood-falls experiments conducted in SW Atlantic. Ontogenetic changes in harpoon chaetae varies from smooth to with two rows of barbs. Diagnosis of the genus emended to include harpoon chaetae with two rows of barbs. Gene order of mitochondrial genome similar to other Amphinomidae.